Profil Pedagang Keliling Di Kelurahan Malalayang Dua Kecamatan Malalayang Kota Manado - Wenda, Yefri; Tambas, Jane Sulinda; Sendow, Martha Mareyke (AGRI-SOSIOEKONOMI, 2023)
The aim of this research is to describe the profiles of peddlers in Malalayang Dua Village, Malalayang District, Manado City. The research was carried out in the Malalayang Dua subdistrict, Malalayang District, Manado City. The research was conducted for three months, from August to October 2022. The data collected in the research were primary data and secondary data. Primary data was collected through direct interviews with mobile vendor respondents and direct field observations to see how mobile vendors interact with their buyers, then data triangulation was used to check data through interviews. Secondary data was obtained from documents from the Malalayang Dua Village which are related to research such as libraries and data from certain relevant agencies. The data analysis method used is descriptive analysis where the collected data will be presented in tabular form and explained in descriptive words. The results of the study show that the profiles of mobile traders in Malalayang Dua Village, Malalayang District, Manado City are traders who sell various kinds of vegetables, spices and fish by traveling around for 8 hours every day. Traders from outside the region (Gorontalo and Makassar) trade in Manado for 7 to 20 years. The motivation to trade is due to encouragement from within and from outside the trader, such as the desire to move forward and generate income and family needs.